2007
DOI: 10.1111/j.1365-2990.2007.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐converting enzyme (ACE) levels and activity in Alzheimer's disease, and relationship of perivascular ACE‐1 to cerebral amyloid angiopathy

Abstract: Our findings indicate that ACE-1 activity is increased in AD, in direct relationship to parenchymal Abeta load. Increased ACE-1, probably of neuronal origin, accumulates perivascularly in severe CAA and colocalizes with vascular ECM. The possible relationship of ACE-1 to the deposition of perivascular ECM remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
151
3
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(173 citation statements)
references
References 65 publications
7
151
3
4
Order By: Relevance
“…In previous post‐mortem studies, ACE‐1 activity was elevated in midfrontal cortex in AD 31, 34, 35. In contrast, both ACE activity (Figure 4A) and the level of its cleavage product Ang II (Figure 4B) were reduced in the precuneus in AD, although only the difference in Ang II concentration was significant ( P  = 0.004).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…In previous post‐mortem studies, ACE‐1 activity was elevated in midfrontal cortex in AD 31, 34, 35. In contrast, both ACE activity (Figure 4A) and the level of its cleavage product Ang II (Figure 4B) were reduced in the precuneus in AD, although only the difference in Ang II concentration was significant ( P  = 0.004).…”
Section: Resultsmentioning
confidence: 62%
“…We showed that Aβ40 upregulated endothelin‐converting enzyme‐1 (ECE1)‐mediated production of EDN1 by cerebrovascular endothelial cells 48, and that Aβ42 upregulated endothelin‐converting enzyme‐2 (ECE2)‐mediated production of EDN1 by neurons 45. Another vasoconstrictor with the potential to exacerbate cerebral hypoperfusion in AD is angiotensin II (Ang II), cleaved from angiotensin I by the action of angiotensin‐converting enzyme (ACE), the level of which was found to be elevated in the frontal cortex in AD 31, 35. ECE1, ECE2 and ACE are all capable of cleaving Aβ, and their upregulation in AD is probably a response to the accumulation of Aβ substrate 33.…”
Section: Introductionmentioning
confidence: 99%
“…We investigated 90 cases of AD and 59 agematched controls whose brains were from people who had no history of dementia and had undergone extensive neuropathological assessment and had few or absent neuritic plaques, a Braak tangle stage of III or less, and no other neuropathological abnormalities. All cases had previous measurements of ACE-1 activity [8,35], total soluble (NP-40-extracted) and insoluble (Guanidine Hydrochloride (GuHcl)-extracted) Aβ levels [36], and tau load (area fraction of cerebral cortex immunopositive for ptau) [37,38] within the mid-frontal cortex (Brodmann area 9). The cohorts were matched closely for age-at-death and post-mortem delay.…”
Section: Case Selectionmentioning
confidence: 99%
“…The left cerebral hemisphere had been sliced and frozen at -80°C until used for biochemical assessment. For each case we dissected 200mg brain tissue from the mid-frontal cortex (Brodmann area 9) that was homogenised in a Precellys homogeniser (Stretton Scientific, Derbyshire, UK) as previously described [8,9]. Brain homogenates were prepared in either 1% SDS lysis buffer (100uM NaCl, 10mM Tris pH 6, 1μM phenylmethylsulfonyl fluoride (PMSF), 1μg/ml aprotinin (Sigma Aldrich) and 1% SDS in distilled water) or 0.5% triton-X100 lysis buffer (20mM Tris pH 7.4, 10% sucrose, 1μM PMSF, 1μg/ml aprotinin (Sigma Aldrich) and 0.5% triton X-100 in distilled water).…”
Section: Brain Tissuementioning
confidence: 99%
See 1 more Smart Citation